Species distribution modelling and landscape connectivity as tools to inform management and conservation for the critically endangered Himalayan brown bear (Ursus arctos isabellinus) in the Deosai National Park, Pakistan - Fida, Tosif; Mohammadi, Alireza; Almasieh, Kamran; Bosso, Luciano; Ud Din, Shams; Shamas, Urwah; Nawaz, Muhammad Ali; Kabir, Muhammad (Frontiers in Ecology and Evolution, 2025)
The main cause of the global threat to large carnivore populations living in high-altitude areas is human pressure. The Himalayan brown bear (Ursus arctos isabellinus, hereafter bear) is listed as a critically endangered species, and it dominates the higher altitudes of the North and Western Himalayan landscapes. Here, we used species distribution modelling and landscape connectivity to find bears’ suitable habitats and corridors in the Deosai National Park (DNP) and surrounding areas. Species distribution models detected a bear’s suitable habitat of 1,125 km2, of which ca. 73% was covered by DNP. The most crucial predictors in determining the bears’ distribution were elevation—particularly if it was between 3,500 and 4,500 meters above sea level—as well as the bears’ distance from rivers, cattle, and the DNP borders. We discovered robust connectivity among presence points in the core of the study area, particularly within the DNP boundaries, by using the electrical circuit theory models. Landscape connectivity values were indeed low in some areas outside and close to the DNP confines. Based on our findings, it is imperative to protect habitats and corridors that allow the bears to migrate between the suitable patches, particularly beyond the park’s boundaries, to improve bear conservation.